ANALYSIS OF THE PROBLEMS OF THE MARKET OF EDUCATIONAL SERVICES AND ITS SPECIFIC CHARACTERISTICS - Mukhammadiev U. A. (European Science Publishing, 2024)
The principles of successful operation of higher education institutions and the market of educational services are studied. Factors affecting the educational services market are presented. The main directions of effective planning of the educational process are analyzed. It is based on the principles of higher education services market formation.
Keywords: Market of educational services, factors of tangible and intangible production of educational services, classification of social sectors.